Innovation in Thermalism: An Example in Beira Interior Region of Portugal - Araújo, André (2016)
Portugal is one of the richest European countries in thermal waters, and the majority of the spas are located inland in the northern and central regions. Thermal spa treatment is a touristic product that is highly recognized for its potential in the exploration of endogenous regional resources. Consequently, the development of new and competitive thermal tourism products can play an important role in the development of the inland regions, contributing effectively to addressing the economic asymmetries of the region. Based on their physico-chemical properties, thermal waters can have different therapeutic indications, including in dermatology. In the region of the Beira Interior there are two spas with thermal water presenting therapeutic dermatological applications, and the use of these waters in dermocosmetic formulations is proposed as one of the most relevant applications of innovation tools in the Thermal Spa sector. A number of cosmetic companies have encapsulated active molecules in nanoscale systems to enhance product performance. The properties of the nanocarriers systems, namely liposomes, polymeric and solid lipid nanoparticles as well nanoemulsions, are fundamental to increase the skin permeation/penetration. Furthermore, these systems have the capacity to preserve the original and unique properties of the thermal water and ensure the stability of the other active components during more time. The development of dermocosmetics based on thermal water carried in nanobiotechnological systems is proposed for its contribution to the differentiation amongst local, unique and genuine products, especially relevant in the case of products with high economic impact in tourism markets.